2006
DOI: 10.1177/070674370605100406
|View full text |Cite
|
Sign up to set email alerts
|

Factors Explaining Career Satisfaction among Psychiatrists and Surgeons in Canada

Abstract: The study demonstrated that variance associated with career satisfaction can be explained using various factors reported directly by physicians. The study also confirmed that relative differences in the importance of these factors do occur among specialties. Surgeons prefer to delegate more responsibility in the management of their practices on an informal basis, whereas psychiatrists prefer to be more involved in the management of their practices and use more formal structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
16
1
6

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 41 publications
3
16
1
6
Order By: Relevance
“…In accordance with this finding, men considered career advice as much more important than women. Our findings are in contrast to those of North American studies, showing that women were less satisfied about career advice than men (Frank et al 1999;Lepnurm et al 2006;Furnham 2008).…”
Section: Discussioncontrasting
confidence: 99%
“…In accordance with this finding, men considered career advice as much more important than women. Our findings are in contrast to those of North American studies, showing that women were less satisfied about career advice than men (Frank et al 1999;Lepnurm et al 2006;Furnham 2008).…”
Section: Discussioncontrasting
confidence: 99%
“…Most previous studies measured physician wellbeing by examining career satisfaction only, 6,7,19 while the literature suggests that work-life balance is increasingly important in medical students' specialty choice and physicians' career commitment. 2,42 Our results suggest that physicians often assess their work satisfaction and life satisfaction differently. For example, income was not significantly associated with most physician well-being measures such as life satisfaction, life meaning, and career commitment, while it has traditionally been thought to be important to physician career satisfaction.…”
Section: Discussionmentioning
confidence: 81%
“…Canadian researchers have compared psychiatrists to surgeons emphasizing that explanatory variables associated with their satisfaction with careers are among others intrinsic and extrinsic rewards and workload. In addition, their study demonstrated that variance associated with career satisfaction can be explained using various factors reported directly by physicians [18]. In Israel the IMA specifically interviewed a representative sample of 500 physicians focusing on professional satisfaction [19].…”
Section: Discussionmentioning
confidence: 99%